The Cooling Effect of Beam Self-Fields on the Photocathode Surface in High Gradient RF Injectors. (November 2019) - Chen, Ye; Krasilnikov, Mikhail; Stephan, Frank
Abstract: The intrinsic slice emittance of the emitted electrons on the photocathode surface at each moment during the transient photoemission process depends on the transverse size of the slice and the mean kinetic energy of the electrons within the slice. The latter relies on the surface barrier potentials of the cathode material at a fixed wavelength of the incident light, and is thus significantly influenced by the presence of strong rf and beam self-fields at /close to the cathode surface. This is, in particular, the case in high brightness injectors for modern free electron lasers. In this article, the beam self-fields are determined in a self-consistent approach, based on which improved transverse and temporal emission distributions are obtained. The nonlinear correlations of the intrinsic surface slice emittance within the bunch are shown for multiple bunch charges. A peak to peak variation of the intrinsic surface emittance is estimated as 30% for the highest charge-density case considered in this paper. An overall reduction of the average intrinsic emittance is computed as 10% accordingly. The cooling effect on the cathode surface is enhanced as the local space-charge density rises. The impacts of the cooling effect on downstream beam qualities are demonstrated through particle tracking simulations based on the injector setup at the Photo Injector Test Facility at DESY in Zeuthen (PITZ).